Public-Private Dialogue in Business Regulation Reform : A Case Study on PEMUDAH - Kuriakose, Smita; Eknath, Varun (World Bank, Washington, DC, 2020)
Traditionally, government and business had few incentives to actively collaborate. For the most part, government regulated business, and business lobbied government on areas of economic interest. When partnerships did occur, they were usually undertaken to invest in large infrastructure projects through formal contractual agreements (Rosenbaum, L., Van Buren, E. and Mennel, J., 2013). With the growing complexity and diversity of socio-economic challenges, the nature of public-private collaborations has seen a fundamental change. Both sides realized that business problems are now government problems—and vice versa—and both are proactively intensifying new approaches to forging partnerships at the highest levels. Consequently, public-private dialogues (PPD) as a form of institutional arrangements have been pivotal in stimulating reform activity and improving a country's investment climate. Against this backdrop, this study explores the key tenets of successful public-private dialogues and its importance in the overall development of an economy in its first chapter. This chapter also seeks to study the various challenges associated with PPDs to caution against their poor administration and consequent threat to diminish the anticipated public good.